Inventor profile mining approach for prospective human resource scouting. Issue 1 (February 2021) - Chung, Jaemin; Ko, Namuk; Kim, Hyeonsu; Yoon, Janghyeok
Highlights: An inventor profiling approach to identify prospective human resources is proposed. Topic modeling and bibliometric analysis are applied to large-scale patent data. Inventors are evaluated based on their invention field, performance, and career. The approach identifies young and talented inventors by firms' technology strategy. The approach can support firms' decision-making process for human resource scouting. Abstract: Scouting young and talented human resources with firm-specific domain knowledge has a great impact on performance and sustainable growth among technology-based firms. Previous studies have proposed key researcher identification and recommendation approaches, but few studies have focused on identifying prospective human resources—young and talented people suitable for a firm's technology strategy. Thus, this study proposes an inventor profile mining approach for identifying such human resources. The proposed approach is as follows: 1) collecting patent data related to a target firm and preprocessing candidate inventors' patents; 2) identifying the inventors' technology fields and measuring their invention performance and career; 3) generating performance-career portfolio maps for invention fields to identify prospective inventors aligned with the target firm's technology development directions. We show that this approach can identify prospective inventors through a case study and statistical validation. This approach is expected to be used as a human resources management tool by technology-based firms to help them identify and scout young and talented human resources the most suitable for technology strategies.